2022
DOI: 10.3390/antiox11020348
|View full text |Cite
|
Sign up to set email alerts
|

Association between Phytochemical Index and Inflammation in Korean Adults

Abstract: While the relationship between phytochemicals and inflammation has been confirmed by in vivo or in vitro studies, large-scale epidemiological studies comprehensively analyzing phytochemical-rich food groups remain scarce. Therefore, we evaluated the association between the phytochemical index (PI) and the inflammation levels in Korean adults. The data were derived from the 2015–2018 Korea National Health and Nutrition Examination Survey, and a total of 18,699 participants were analyzed. High-sensitivity C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Higher amount of lycopene consumption, a kind of phytochemical, was associated with lower hs-CRP levels 33 . Kim et al reported an inverse relationship between DPI scores and the likelihood of increasing hs-CRP levels in their study of 18,699 over-19 years Koreans from 2015 to 2018 34 . Results from other studies match these current findings 33 , 35 , 36 .…”
Section: Discussionmentioning
confidence: 93%
“…Higher amount of lycopene consumption, a kind of phytochemical, was associated with lower hs-CRP levels 33 . Kim et al reported an inverse relationship between DPI scores and the likelihood of increasing hs-CRP levels in their study of 18,699 over-19 years Koreans from 2015 to 2018 34 . Results from other studies match these current findings 33 , 35 , 36 .…”
Section: Discussionmentioning
confidence: 93%
“…Using the Food Composition Table 10.0 version of the National Institute of Agricultural Sciences under the Rural Development Administration and the Computer Aided Nutritional Analysis Program 5.0 of the Korean Nutrition Society [ 36 , 37 ], we constructed an updated nutrient database of phytochemical-rich foods, which included whole grains, fruits, vegetables, pulses, nuts, and seaweed [ 21 , 23 , 24 , 38 ]. To calculate the PI, the total calorie intake from dietary phytochemical-rich foods was divided by the overall daily calorie intake, as previously described in the literature [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The phytochemical index (PI) has been recently proposed as a surrogate marker to reflect the levels of phytochemical intake [ 21 , 22 ]. Several epidemiological studies have shown that higher PI is associated with a reduction in inflammation, hypertension, diabetes, metabolic syndrome, and stroke [ 21 , 23 , 24 , 25 , 26 ]. A recent meta-analysis confirmed that PI is inversely associated with obesity and overweight, with higher PI levels being observed in groups with lower rates of obesity and overweight [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the dietary phytochemical index (PI) is a suitable tool to evaluate the received amount of phytochemicals ( 20 ). Phytochemicals, which are bioactive chemicals in antioxidant-rich foods, as anti-inflammatory agents and antioxidants, play beneficial roles in OS, immunity, and inflammation status ( 21 ).…”
Section: Introductionmentioning
confidence: 99%